Learning Management System Implementation in Online Education: A Case Study on Student Psychological Dynamics - Nabrisi Rohid; Nibrosu Rohid; Daniel Susilo; Sukisno Sukisno (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2026)
The rapid advancement of digital technology has transformed higher education, particularly through the implementation of Learning Management Systems (LMS) in online learning. LMS functions not only as a technological tool but also as a psychological environment that influences how students regulate their learning, interpret academic experiences, and manage emotional responses. Therefore, this study aims to explore students’ psychological dynamics in LMS-based learning, focusing on psychological adaptation, learning motivation, and emotional well-being within digital learning environments. This study employed a qualitative approach using Interpretative Phenomenological Analysis (IPA) to understand how students subjectively construct meaning from their lived experiences in online learning. Data were collected through in-depth semi-structured interviews with students who actively used LMS and analyzed through iterative reading, coding, and thematic development to identify core psychological themes. The findings revealed three major themes: psychological adaptation and self-regulation, student motivation and engagement, and emotional experience and psychological well-being. Initially, students experienced confusion and difficulty managing independent learning; however, over time, they developed greater autonomy, self-discipline, and academic confidence. LMS enhanced motivation through flexible access, interactive features, and feedback, although technical challenges occasionally caused frustration and reduced engagement. Additionally, LMS provided emotional comfort and flexibility but also introduced risks of isolation and digital fatigue. The implications of this study suggest that LMS should be understood not only as an instructional technology but also as a psychological learning environment that shapes students’ cognitive, emotional, and motivational development.Perkembangan pesat teknologi digital telah mentransformasi sistem pendidikan tinggi, khususnya melalui implementasi Learning Management System (LMS) dalam pembelajaran daring. LMS tidak hanya berfungsi sebagai alat teknologi, tetapi juga sebagai lingkungan psikologis yang memengaruhi bagaimana mahasiswa mengatur pembelajaran, memaknai pengalaman akademik, serta mengelola respons emosional mereka. Oleh karena itu, penelitian ini bertujuan untuk mengeksplorasi dinamika psikologis mahasiswa dalam penggunaan LMS, khususnya terkait adaptasi psikologis, motivasi belajar, dan kesejahteraan emosional dalam lingkungan pembelajaran daring. Penelitian ini menggunakan pendekatan kualitatif dengan metode Interpretative Phenomenological Analysis (IPA) untuk memahami bagaimana mahasiswa memaknai pengalaman belajar mereka secara subjektif. Data dikumpulkan melalui wawancara mendalam semi-terstruktur dengan mahasiswa yang aktif menggunakan LMS, kemudian dianalisis melalui proses membaca berulang, pengkodean, dan pengembangan tema psikologis utama. Hasil penelitian menunjukkan tiga tema utama, yaitu adaptasi psikologis dan regulasi diri, motivasi dan keterlibatan belajar, serta pengalaman emosional dan kesejahteraan psikologis. Mahasiswa awalnya mengalami kebingungan dan tantangan dalam mengelola pembelajaran secara mandiri, namun secara bertahap mengembangkan kemandirian, disiplin diri, dan kepercayaan diri akademik. LMS juga meningkatkan motivasi melalui fleksibilitas akses, fitur interaktif, dan umpan balik, meskipun tantangan teknis terkadang menimbulkan stres. Selain itu, LMS memberikan kenyamanan emosional, tetapi juga dapat memunculkan perasaan isolasi dan kelelahan digital. Implikasi penelitian ini menunjukkan bahwa LMS harus dipahami tidak hanya sebagai sistem teknologi, tetapi sebagai lingkungan psikologis yang memengaruhi perkembangan kognitif, emosional, dan motivasional mahasiswa.